Effects of Cell Phone Dependence on Mental Health Among College Students During the Pandemic of COVID-19: A Cross-Sectional Survey of a Medical University in Shanghai - Xu, Ting; Sun, Xiaoting; Jiang, Ping; Chen, Minjie; Yue, Yan; Dong, Enhong (Frontiers in Psychology, 2022)
Objective: To investigate the effects of cell phone dependence (CPD) on mental health among undergraduates during COVID-19 pandemic, and further identify the determinants that may affect their mental health in China. Methods: The data were collected from 602 students at a medical school in Shanghai via an online survey conducted from December 2021 to February 2022. The Mobile Phone Addiction Index and Depression Anxiety Stress Scale (DASS) were applied to evaluate CPD and meatal health, respectively. Independent sample t test and One-way analysis of variance (ANOVA) were employed to compare the means of continuous variables among categorical groups. Correlations between continuous variables were detected using Pearson’s correlation analysis. Univariable and multivariable logistic regressions were employed to identify the determinants of mental health. Results: Among the 402 eligible students, 73.88% were females with an average age of the 20.19± 2.36 years. On average, the DASS score was 32.20 ± 11.07, the CPD score was 36.23±11.89, and the cell phone use duration was 7.67 ± 3.61 hours/day. CPD was found to have negative effect on mental health among college students in Shanghai. Additionally, cell phone use duration, age, being senior students, faculty-student relationship, insomnia, tobacco use, obesity, and life satisfaction were clarified as contributing factors of mental health among college students. Conclusion: High degree of CPD could have negative effect on college students’ mental health, which might lead to some psychological problems. Appropriate actions and effective interventions are highly needed to prevent severe psychological injuries among college students in China.